Singular and fractal properties of distributions of random variables digits of polybasic representations of which a form homogeneous Markov chain - Pratsiovytyi, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We study the fractal properties of distributions of random variables digits of polybasic Q-representations (a generalization of n-adic digits) of which form a homogeneous Markov chain in the case where the matrix of transition probabilities contains at least one zero.